Life after Child Care Institution: Emotional Intelligence and Achievement Motivation among Reintegrated Children in Malawi, Africa - Limbani, Trophina Ruthian; Sharma, Hariom; Naz, Samreen (International Journal of Psychosocial Rehabilitation, 2020)
The current study aimed to compare the emotional intelligence and achievement motivation and relationship among these constructs of children in child care institutions and family based reintegrated children. 120 children, age range 10- 17 years from Blantyre district and Lilongwe district in the southern and central region of Malawi, Africa were selected using convenience sampling. Achievement Motive test by Bhargava and Emotional Intelligence Scale by Hyde, Pethe and Dhar were administered. Collected data were treated with statistics of Mean, SD, t-test, Pearson correlation and two-way ANOVA. Findings revealed insignificant differences among emotional intelligence (t=1.86, df=118, p=0.06) and achievement motivation (t=0.98, df=118, p=0.33) of family based reintegrated children and children in child care institution. However, significant positive relationship (r=0.291, p value <0.05) between emotional intelligence and achievement motivation was observed for family based reintegrated children but insignificant relationship (r=0.070, p value = 0.595) for child care institution children. Furthermore, findings demonstrated an insignificant difference between emotional intelligence and achievement motivation with regard to gender among family based reintegrated children and child care institution children.